Case Report: Malignant transformation of maxillary giant cell tumor of bone from EURACAN reference center - Federica Riva; Sabrina Vari; Concetta Elisa Onesti; Renato Covello; Silvia Scuderi; Serena Ceddia; Maria Rosaria Fiore; Vincenzo Anelli; Sabino Strippoli; Virginia Ferraresi (Frontiers in Oncology, 2025)
Giant cell tumor of bone (GCTB) is a benign but locally aggressive neoplasm that can rarely undergo malignant transformation, with a poor prognosis. The most frequent histotypes of the sarcomatous transformation of GCTB are osteosarcoma, fibrosarcoma, and undifferentiated pleomorphic sarcoma, and the treatment approach mirrors that of high-grade sarcomas. This case report describes the malignant transformation of a maxillary GCTB treated with standard systemic treatments for bone tumors and local treatment, resulting in a progression of disease until the patient’s death. Nevertheless, a marked radiological and clinical response was achieved with local carbon ion therapy. This case highlights the diagnostic and therapeutic challenges of malignant transformation of GCTB, emphasizing the importance of a multidisciplinary approach at specialized centers and the potential role of local therapies in selected cases.